Parsing Croatian and Serbian by Using Croatian Dependency Treebanks - Agić, Željko; Berović, Daša; Merkler, Danijela (2013)
We investigate statistical dependency parsing of two closely related languages, Croatian and Serbian. As these two morphologically complex languages of relaxed word order are generally under- resourced -- with the topic of dependency parsing still largely unaddressed, especially for Serbian -- we make use of the two available dependency treebanks of Croatian to produce state-of- the-art parsing models for both languages. We observe parsing accuracy on four test sets from two domains. We give insight into overall parser performance for Croatian and Serbian, impact of preprocessing for lemmas and morphosyntactic tags and influence of selected morphosyntactic features on parsing accuracy.
Projekt MZOS
ENG